2021
DOI: 10.3389/fpsyg.2021.645754
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Social Distancing During the COVID-19 Pandemic on Anxiety and Eating Behavior—A Longitudinal Study

Abstract: As social animals, humans need to live in groups. This contact with conspecifics is essential for their evolution and survival. Among the recommendations to reduce transmission of the new coronavirus (SARS-CoV-2) responsible for COVID-19 are social distancing and home confinement. These measures may negatively affect the social life and, consequently, the emotional state and eating behavior of individuals. We assessed the impact of the COVID-19 pandemic on the anxiety, premenstrual symptoms, and eating behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 78 publications
(118 reference statements)
0
13
0
2
Order By: Relevance
“…Likewise, a negative relationship is also observed between anxiety and the development of physical and social self-concept, with a lower level of correlation for the latter. Dolenc (2019) (Voulgaridou & Kokkinos, 2020), affecting the development of social self-concept (Freitas et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a negative relationship is also observed between anxiety and the development of physical and social self-concept, with a lower level of correlation for the latter. Dolenc (2019) (Voulgaridou & Kokkinos, 2020), affecting the development of social self-concept (Freitas et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It was further reported that female healthcare workers in Turkey had an association between the COVID-19 pandemic-induced anxiety, perceived stress, depressive symptoms, and increased prevalence of menstrual cycle irregularity (Takmaz, Gundogmus, Okten, & Gunduz, 2021). A longitudinal study in Brazil before and during pandemic also showed that the total premenstrual screening tool score showed no change in the presence and severity of premenstrual symptoms between the two periods, but that the "anxiety/stress" symptoms of this tool revealed that it was more severe in the students before the pandemic (Freitas, de Medeiros, & Lopes, 2021). Thus, stress and anxiety may be related to menstrual abnormality during the pandemic.…”
Section: Introductionmentioning
confidence: 97%
“…There were also seen to be PMS effects of low academic concentration, a decrease in performance, and restricting social activities (21). In recent studies of the psychological and social effects of COVID-19, it has been shown that this disease has led to many radical changes in societal living conditions and these are associated with negative psychological outcomes (22,23). For example, in a study of 1210 subjects in China during the COVID-19 pandemic, 16.5% of the subjects were found to have moderate and severe depression symptoms and 28.8% had moderate and severe anxiety symptoms (24).…”
Section: Resultsmentioning
confidence: 99%